The Role of Purchase Intent in the Relationship of Brand Awareness and Brand Loyalty in E-Wallet Users - Raffly Pratama Kusnawan (LPPM Universitas Buddhi Dharma, 2026)
The development of non-cash transactions in Indonesia shows significant growth in line with the increasing use of the internet and digital technology. One of the prominent innovations is digital wallet (e-wallet) services such as OVO, GO-PAY, and DANA which now dominate the national market. This study aims to analyze the impact of brand awareness on brand loyalty through purchase intentions in e-wallet users. The study used a quantitative approach with a survey method and the distribution of questionnaires to 120 respondents in Tangerang City. The data was analyzed using Structural Equation Modelling (SEM) based on Partial Least Square (PLS) by testing the outer model, inner model, and mediation analysis through the Variance Accounted For (VAF) method. The results of the study show that brand awareness has a significant effect on brand loyalty and purchase intent. Meanwhile, purchase intent acts as a partial mediating variable between brand awareness and brand loyalty. These findings reinforce the importance of e-wallet companies' strategies in building brand awareness to drive repeat purchase intent which ultimately increases brand loyalty. This research also provides practical implications for e-wallet providers to focus on consistent marketing communication strategies, as well as theoretical for the development of literature on consumer behavior in the digital age.